Biotechnological aspects of plum pox virus - López-Moya, Juan J.; Fernandez-Fernandez, M. R.; Cambra, Mariano; Garcia, Juan Antonio (2017)
Plum pox potyvirus (PPV), the causal agent of a devastating disease that affects stone fruit trees, is becoming a target of intense studies intended both to fight against viral infection and to develop practical applications based on the current knowledge of potyvirus molecular biology. This review focuses on biotechnological aspects related to PPV, such as novel diagnostic techniques that facilitate detection and typing of virus isolates, strategies to implement pathogen-derived resistance through plant transformation, the potential use of genetic elements derived from the virus, and the recent development of PPV-based expression vectors.